Low carbonyl reductase 1 expression is associated with poor prognosis in patients with oral squamous cell carcinoma - Yamanouchi, Ryota (Mol Clin Oncol, 2018)
Carbonyl reductase 1 (CBR1) is an enzyme that catalyzes the reduction of numerous compounds by using NADPH-dependent oxidoreductase activity. Decreased expression of CBR1 is associated with disease progression and an unfavorable outcome in several types of malignancies. The purpose of the current study was to determine whether CBR1 expression could be a useful prognostic factor in patients with oral squamous cell carcinoma (OSCC). Therefore, its mechanisms of action were investigated in order to understand how CBR1 affects cancer cell behavior in vitro. CBR1 expression was evaluated using immunohistochemistry and tissue samples obtained from 90 patients with OSCC. The associations between CBR1 expression, clinicopathological characteristics and patient survival were also analyzed. In addition, the role of CBR1 in cancer cell invasion and metastasis was examined, along with its underlying molecular mechanisms, via transfecting CBR1-siRNA into the HSC2 human OSCC cell line. Immunohistochemical analysis revealed that biopsy tissue samples of 71.1% of the patients with OSCC were positive for CBR1. In addition, CBR1 expression status was correlated with the N classification (P<0.0001), stage (P=0.0018) and outcome (P=0.0095). Furthermore, a statistical correlation was determined between the protein expression status and overall survival (P=0.0171). In vitro studies indicated that the suppression of CBR1 by CBR1-siRNA increased cancer cell proliferative, wound healing and migratory abilities. These findings suggest that low expression levels of CBR1 may affect cancer prognosis, and that CBR1 may have potential as a prognostic factor for patients with OSCC.